MAINTAINING EMPLOYEE RETENTION AND EMPLOYEE ENGAGEMENT IN FAMILY- OWNED MSMES IN INDONESIA THROUGH COMPENSATION AND LEADER COMPETENCE - Maria Imelda Novita Susiang (CV. Adiba Aisha Amira, 2025)
This study explores the complex dynamics of sustaining worker engagement and retention in family-run Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia, emphasizing the functions of leader competency and remuneration. 245 individuals from different family-owned MSMEs participated in the study, which used a quantitative methodology. To examine the connections between pay, leader competency, employee retention, and engagement, structural equation modeling (SEM) with partial least squares (PLS) was used. Strong validity and reliability were demonstrated by the measurement model, validating the applicability of the selected indicators. The structural model showed that there are strong positive correlations between pay, the ability of leaders, and employee engagement and retention. These results were also strongly impacted by the interaction effects of leader competency and compensation. The adequacy of the suggested model was confirmed by the goodness-of-fit indexes. By offering factual support and practical advice for family-owned MSMEs looking to improve employee engagement and retention, our findings add to the body of literature already in existence.